Cable‐like V2O5 Decorated Carbon Cloth as a High‐Capacity Cathode for Flexible Zinc Ion Batteries. Issue 5 (23rd March 2022) - Wang, Yingchao; Jiang, Guangshen; Zhang, Zhuo; Chen, Hanchu; Li, Yutong; Kong, Debin; Qin, Xin; Li, Yanyan; Zhang, Xinghao; Wang, Hui
Abstract : Rechargeable Zn‐ion batteries (ZIBs) are regarded as one of the most promising energy storage systems due to their non‐toxicity, low cost, and non‐flammability features. However, exploring flexible and high‐capacity devices with prominent cycling still remains a challenge for ZIBs. Herein, a flexible and binder‐free carbon cloth coated by V2 O5 (namely, CC@V2 O5 ) cathode material is prepared through a simple solvothermal method. The cable‐like CC@V2 O5 provides abundant active sites and highways for electrons transport. Meanwhile, the layered structure of V2 O5 can also facilitate zinc ion diffusion. The galvanostatic intermittent titration technique indicates that the zinc‐ion diffusion coefficient of CC@V2 O5 is much higher than that of the commercial V2 O5 . As a result, the CC@V2 O5 exhibits excellent electrochemical performance and outstanding bendability arising from the synergistic effect between porous V2 O5 and carbon cloth, in terms of a remarkable discharge capacity (296 mAh g −1 at 3 A g −1 ), superior rate capability (241 mAh g −1 at 5 A g −1 ), and long‐term stability with a capacity retention of 87.1% over 2200 cycles. The novel strategy proposed in this study may provide guidance for exploiting high‐performance flexible systems and wearable energy storage systems. Abstract : A flexible and binder‐free carbon cloth coated by V2 O5 (namely, CC@V2 O5 ) cathode material is prepared through a simple solvothermal method. The cable‐like cathode is demonstrated to provide abundant active sites, and confer efficient electron and ion transport frameworks toward flexible zinc‐ion batteries.